Improving anaerobic fitness in young basketball players: Plyometric vs. specific sprint training - Gottlieb, R.; Eliakim, A.; Shalom, A.; Dello Lacono, A.; Meckel, Y. (Journal of Athletic Enhancement, 2014)
Basketball is a game that is typically performed in an intermittent manner, and includes numerous bursts of explosive activity. Thus, implementation of training methods that best develop anaerobic fitness is of significant importance to basketball coaches and players. The aim of the present study was to compare the effect of plyometric and specific sprint training, matched for total volume, on the anaerobic fitness of young basketball players. Nineteen young (16.3 ± 0.5 years) male basketball players were randomly assigned to either a plyometric training group or a specific sprint training group, and completed two similar fitness tests prior to and following six weeks of training. The two training programs consisted of plyometric jump training (4 sets of 4-6 series with 6 jumps each) and specific sprint training (4 sets of 4-6 × 20 m repetitions). Prior to training there were no baseline differences between the groups in 20 m sprint time (speed test), bounding distance and vertical jump height (power tests), 2×5 m run time (agility test) or suicide run time (basketball-specific anaerobic endurance test). Plyometric training led to a significant improvement only in the suicide test time (1.6 ± 1.6%, p<0.05). Specific sprint training led to a significant improvement in the 20 m sprint time (2.6 ± 1.7%), bounding distance (3.9 ± 3.8%), and suicide test time (1.2 ± 1.1%, p<0.05 for all). However, there was no significant between-group differences in the training effects on any of the anaerobic variables measured. Neither training program had a significant effect on jump height or the 2×5 m run. The study showed that plyometric training and specific sprint training do not differ statistically in enhancing anaerobic fitness of young basketball players. Thus, coaches may have the possibility of alternating between these methods during the busy basketball season.